A preliminary study of bipolar disorder type I by mass spectrometry-based serum lipidomics. (December 2017) - Ribeiro, Henrique C.; Klassen, Aline; Pedrini, Mariana; Carvalho, Michelle S.; Rizzo, Lucas B.; Noto, Mariane N.; Zeni-Graiff, Maiara; Sethi, Sumit; Fonseca, Francisco A.H.; Tasic, Ljubica; Hayashi, Mirian A.F.; Cordeiro, Quirino; et al.
Abstract: The present study aimed at investigating possible alterations in the serum lipid profile of euthymic patients with bipolar disorder type I (BD) compared to healthy controls (HC). Thirty-five individuals from both genders were recruited, with 14 diagnosed and treated as BD patients (BD group) and 21 healthy subjects (HC group). Clinical assessment was based on the Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I), Young Mania Rating Scale (YMRS), and 17-items of Hamilton Depression Rating Scale (HDRS-17) data, which were used to confirm diagnosis, to verify psychiatric comorbidities, and to estimate the severity of manic and depressive symptoms. Ultra-high performance liquid chromatography (UHPLC) coupled to high resolution mass spectrometry (HRMS) was applied to analyze the lipids extracted from all serum samples from both studied groups. In this pioneer and exploratory study, we observed different serum lipid profiles for BD and HC groups, especially regarding glycerophospholipid, glycerolipid, and sphingolipid distribution. Multivariate statistical analyses indicated that 121 lipids were significantly different between BD and HC. Phosphatidylinositols were identified as the most altered lipids in BD patient sera. The results of this preliminary study reinforce the role of lipid abnormalities in BD and offer additional methodological possibilities for investigation in the field. Highlights: Evaluation of the serum lipid profile of bipolar disorder (BD) patients. Serum analyzed by liquid chromatography and high resolution mass spectrometry (MS). Significant differences in lipid profile for BD patients in comparison to controls. Glycerophospho-, glycero-, and sphingolipids were the most altered classes in BD. First report of a MS-based untargeted lipidomics strategy applied to study BD.